STRATEGIC MANAGEMENT: FORMATION AND DEVELOPMENT - E. Rozhkova; A. Sazanova (Вестник университета)
The authors examine the development of the Russian and foreign schools of strategic management, identify the main stages in the development of strategic management, their causes and consequences.